Financial capacity and the demand for audit quality - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2022)
Prior research documents that financial capacity could be positively or negatively associated with the demand for audit quality. We re-examine this relation using changes in local real estate prices as exogenous shocks to corporate financial capacity. Using auditor size, auditor industry specialisation, and auditor fees as measures of audit quality, we find robust evidence that an increase (decrease) in financial capacity significantly reduces (increases) the demand for audit quality, and that this relation is more pronounced when firms are more financially constrained, when external monitoring by institutional investors and financial analysts is weaker, and when there is more negative news about real estate price changes. Our study enriches the related literature by describing a more complete and dynamic relationship between audit quality and financial capacity.